Growth and nutritional status of the first six months of life among selected hospitals: Nairobi Province - Lakati, A.; Makokha, A.; Binns, Colin; Kombe, Y. (2013)
BACKGROUND: Exclusive breastfeeding for infants is recommended for the first six months for optimal health, development and growth. However, there is limited data on infant feeding practices and nutrition status of infants in Nairobi.OBJECTIVE: To assess infant growth and nutritional status and compare with feeding practices in the first six months of life in selected hospitals, Nairobi Province.DESIGN: Prospective cohort designSETTING: Five major hospitals in Nairobi namely; The Aga Khan, Pumwani Maternity, Mater Misercordiae, St Mary's Langata and Jamaa Hospitals.SUBJECTS: A sample of 692 mother-infant pairs were recruited at birth and followed up until six months.INTERVENTION: There was no direct experimental intervention, but there was observation of infant feeding practices, weight and height measurement was recorded every four weeks and determination of nutrition status of the infants for a period of six months.MAIN OUTCOME MEASURES: Nutritional status and infant feeding practices in the first six months.RESULTS: Slightly more than half (58.8%) of the mothers were formally employed and the rest were self employed. The mean age of the mothers was 28.3 ± 4.9 years. The mean income was KES 26,360 ± 34,696. The mean birth weight of infants was 3.24 ± 0.43 kg and 53.3% of all infants were male. Above 80% of infants were within normal weight based on weight for age Z-scores (WAZ) at 6, 10, 14 and 23 weeks. The prevalence of overweight based on WAZ was 9.5%, 11.6%, 11.9% and 11% at 6, 14, 19 and 23 weeks, respectively. There were no significant (P > 0.05) differences in WAZ between infants on different feeding methods.CONCLUSIONS: There was no significant difference in weight or length gain among children that were fully breastfed in comparison to those who were given infant formula or had mixed feeding. However, there was concern over the proportion of overweight infants, as the condition may lead to long term health problems.